A windowing technique for optimal time-frequency concentration and aci rejection in ofdm-based systems - Güvenkaya, Ertu?rul; Şahin, Alphan; Bala, Erdem; Yang, Rui; Arslan, Hüseyin (Institute of Electrical and Electronics Engineers, 2015)
In this paper, we introduce a windowing technique, which provides optimal time-frequency containment and maximal adjacent channel interference (ACI) rejection for orthogonal frequency-division multiplexing (OFDM)-based systems. Instead of using a single pulse shape function for all subcarriers, multiple functions are considered in order to maximize the time-frequency containment of the OFDM waveform. The main strategy is to concentrate the spectrum of windowing functions into a given bandwidth while achieving maximum suppression in the out-of-band region. This is achieved by employing prolate-based windowing functions which give optimal spectral concentration for time-limited pulse shapes. The windowing functions are designed per-subcarrier basis in order to exploit available concentration band for each subcarrier. In addition, the proposed concept is considered for the receive filtering in the presence of ACI. It is shown that the optimal spectral concentration property also maximizes ACI rejection for OFDM receivers.
WOS: 000366928600028
Keywords: ACI; OFDM; Spectral Concentration; Windowing